Drug delivery system based on dendritic nanoparticles for enhancement of intravesical instillation - Qiu X (Dove Medical Press, 2017)
Xuefeng Qiu,1,2,* Kai Cao,1,2,* Tingsheng Lin,1,2 Wei Chen,1 Ahu Yuan,2 Jinhui Wu,2 Yiqiao Hu,2 Hongqian Guo1 1Department of Urology, Drum Tower Hospital, Medical School of Nanjing University, Institute of Urology, Nanjing University, Nanjing, China; 2State Key Laboratory of Pharmaceutical Biotechnology, Medical School of Nanjing University, Nanjing, China *These authors contributed equally to this work Abstract: Intravesical instillation of antitumor agents following transurethral resection of bladder tumors is the standard strategy for the treatment of superficial bladder cancers. However, the efficacy of current intravesical instillation is limited partly due to the poor permeability of the urothelium. We therefore aimed to develop a high-penetrating, target-releasing drug delivery system to improve the efficacy of intravesical instillation. PAMAM, a dendrimer, were conjugated with polyethylene glycol (PEG) to form PEG-PAMAM complex as a nanocarrier. Doxorubicin (DOX) was then encapsulated into PEG-PAMAM to generate DOX-loaded PEG-PAMAM nanoparticles (PEG-PAMAM-DOX). Our results indicated that the PEG-PAMAM was a stable nanocarrier with small size and great biosafety. The release of DOX from PEG-PAMAM-DOX was sluggish but could be effectively triggered in an acid microenvironment (pH =5.0). As a drug carrier, PEG-PAMAM could penetrate mice bladder urothelium effectively and increase the amount of DOX within the bladder wall after intravesical instillation. The antitumor effect of PEG-PAMAM-DOX was evaluated using an orthotopic bladder cancer model in mice. Compared to free DOX, PEG-PAMAM-DOX showed significantly improved efficacy of DOX for intravesical instillation with limited side effects. In conclusion, we successfully developed a PEG-PAMAM-based drug delivery system to enhance the antitumor effect of intravesical instillation. Keywords: bladder cancer, intravesical instillation, chemotherapy, dendrimer, PAMAM, penetration, acid microenvironment, target-releasing